Novel pre-clamp lap joint for CFRP plates: Design and experimental study. (15th December 2022) - Ding, Guozhen; Feng, Peng; Wang, Yu; Ai, Pengcheng
Abstract: Carbon fiber reinforced polymer (CFRP) plates have broad application prospects in civil engineering, but the lack of effective connection will hinder their application. In this paper, a novel lap joint for CFRP plates called a pre-clamp lap joint is proposed. According to the clamp device characteristics, three types of pre-clamp lap joints were tested: planar, curved and thickened. The mechanical performance of these pre-clamp single lap joints was investigated by experiments and finite element analysis. The failure behavior was monitored nondestructively by acoustic emission. The results show that the bolt preload, clamp device type, and adhesive application method are the main factors affecting the mechanical performance of the joints. It was demonstrated that using a reasonable bolt preload and adhesive application method, the curved pre-clamp single lap joint and thickened pre-clamp joint can realize the failure mode of CFRP plate rupture rather than joint failure.